Aeolian landforms within the inactive valley of the middle Warta River section (Central Poland) - Dzieduszyńska, Danuta; Petera-Zganiacz, Joanna (Acta Geographica Lodziensia, 2024)
The article presents the features of the geomorphological landscape dominated by sand covers and dunes within the inactive middle Warta River valley. Detailed geological and geomorphological mapping, sedimentological analysis and age determinations using 14C and OSL methods allowed their formation to be placed in the late Weichselian/early Holocene and the late Holocene. It was found that the nature of aeolian processes is the result of local aerodynamic conditions, the presence of alluvia and fluvioglacial deposits, and substrate moisture.